2023
DOI: 10.3390/microorganisms11030662
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Vaginal Microbiota and Chlamydia trachomatis as Crucial Co-Causative Factors in Cervical Cancer Genesis Procured by HPV

Abstract: Chlamydia trachomatis and human papillomavirus (HPV) are the most common pathogens found in sexually transmitted infections (STIs), and both are known to increase the risk of cervical cancer (CC) and infertility. HPV is extremely common worldwide, and scientists use it to distinguish between low-risk and high-risk genotypes. In addition, HPV transmission can occur via simple contact in the genital area. From 50 to 80% of sexually active individuals become infected with both C. trachomatis and HPV viruses durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 58 publications
0
20
0
1
Order By: Relevance
“…The co-infection of CT and HPV (especially the 16, 18, 31, 33, 53, and 56 genotypes) is considered the most important risk factor for the development of cervical cancer. 228 During the initial stages of HPV infection, LCs play a critical role in initiating the immune response against the virus. 249 They present antigens to T cells, and help immune system to recognize and eliminate the virus.…”
Section: Hpv/ct Co-infection and Immune Responsementioning
confidence: 99%
See 4 more Smart Citations
“…The co-infection of CT and HPV (especially the 16, 18, 31, 33, 53, and 56 genotypes) is considered the most important risk factor for the development of cervical cancer. 228 During the initial stages of HPV infection, LCs play a critical role in initiating the immune response against the virus. 249 They present antigens to T cells, and help immune system to recognize and eliminate the virus.…”
Section: Hpv/ct Co-infection and Immune Responsementioning
confidence: 99%
“…Furthermore, several studies demonstrated an association between HPV/CT co‐infection and developing abnormal cervical cytology and dysplasia 213,226,227 . The HPV and CT DNAs can be detected in approximately 99% of cervical cancer cases 228,229 . There is a mutual benefit in HPV/CT co‐infection.…”
Section: Microbiome and Hpvmentioning
confidence: 99%
See 3 more Smart Citations